1981
DOI: 10.1037/0022-3514.41.4.710
|View full text |Cite
|
Sign up to set email alerts
|

Victim reactions in aggressive erotic films as a factor in violence against women.

Abstract: The present study was designed to investigate whether the behavioral characteristics of the people in erotic films and the nature of the targets available for aggression afterward can affect subsequent aggression. In Experiment 1, male subjects were angered by a male or female confederate. They were then shown a neutral film or one of three erotic films. The erotic films differed in terms of their aggressive content (two were aggressive and one was nonaggressive) and the reactions of the female victim in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(103 citation statements)
references
References 22 publications
2
98
0
1
Order By: Relevance
“…One problem with this study is that the misogynous songs used in the experiment, "suggested that women enjoy coercive sex" (p. 200). It is thus difficult to determine if the results were due to listening to violent lyrics, to the effect of portraying women as enjoying violent sex (e.g., Donnerstein, 1980;Donnerstein & Berkowitz, 1981), or to a potential interaction of these two factors. In addition, because only rap music was used, it is unclear whether the effects would generalize to other genres of music.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One problem with this study is that the misogynous songs used in the experiment, "suggested that women enjoy coercive sex" (p. 200). It is thus difficult to determine if the results were due to listening to violent lyrics, to the effect of portraying women as enjoying violent sex (e.g., Donnerstein, 1980;Donnerstein & Berkowitz, 1981), or to a potential interaction of these two factors. In addition, because only rap music was used, it is unclear whether the effects would generalize to other genres of music.…”
Section: Discussionmentioning
confidence: 99%
“…Research using sexually explicit videos has shown that even unprovoked males will aggress against a female confederate after they watch violent pornography that portrays a woman enjoying violent sex (e.g., Donnerstein, 1980;Donnerstein & Berkowitz, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…230 In the study, men were either angered or treated fairly by fellow study participants prior to what they believed was the experiment. Both groups of men were then shown films that depicted consensual sexual activity or rape scenes.…”
Section: B the "Pornographic Vignette"mentioning
confidence: 99%
“…In order for rape to occur in society, individuals would have to be exposed to rape depictions or taught that rape is an acceptable form of behavior. Research has shown that certa!n types of pornography promote aggressive behavior (Donnerstein & Berkowitz, 1981).…”
Section: Rape As Learned Behaviormentioning
confidence: 99%
“…Similarly, Donnerstein and Berkowitz (1981) found that previously angered males who had viewed a violent pornographic film delivered higher levels of shock to female targets than to male targets. They also found that regardless of whether male subjects had viewed positive or negative outcomes in violent pornographic film.…”
mentioning
confidence: 99%